2004
DOI: 10.1007/s00066-004-1224-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of Tumor Recurrences Following Fractionated Radiotherapy of Primary Tumors

Abstract: In R1H rhabdomyosarcomas tumor oxygenation in recurrent tumors following radiation therapy is significantly lower than in primary tumors. This observation has to be taken into account in cases of tumor recurrences where repeated radiotherapy, chemotherapy or combined treatment modalities are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The resulting heterogeneity response may have further implications on treatment outcome and survival. Such spatial heterogeneity of treatment response in a single tumor has been reported widely for various types of cancer [43,44], including NPC [45].…”
Section: Discussionmentioning
confidence: 98%
“…The resulting heterogeneity response may have further implications on treatment outcome and survival. Such spatial heterogeneity of treatment response in a single tumor has been reported widely for various types of cancer [43,44], including NPC [45].…”
Section: Discussionmentioning
confidence: 98%
“…The potential to improve local control and survival by hypoxia modification was demonstrated by a meta-analysis of 83 clinical trials [23]. Tumor hypoxia is determined in a number of clinical and experimental settings [1,17,22,40] and correction for hypoxia is an important issue in the clinic [2,7]. A number of therapeutic strategies have been established to determine and to overcome tumor hypoxia by improving oxygen supply either by oxygen or carbogen breathing or by increasing the hemoglobin level and oxygen delivery [6,16,30].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of tumor cells to radiotherapy has been shown to be about three times as great when irradiated in a well oxygenated medium as under anoxic condition 29 . Another similar study on R1H Rhabdomyosarcoma of rats reported that in contrast to primary tumors, tumor recurrences had lower oxygenation and responded poorly on irradiation 30 . A few direct clinical human trials have further consolidated role of ozone as an adjuvant therapy in cancer treatment.…”
Section: Clinical Evidence Of Ozone Therapy In Cancer Patientsmentioning
confidence: 84%